A review of carbon materials and their composites with alloy metals for sodium ion battery anodes. (March 2016) - Balogun, Muhammad-Sadeeq; Luo, Yang; Qiu, Weitao; Liu, Peng; Tong, Yexiang
Abstract: Sodium ion batteries are currently emerging as a replacement for lithium ion batteries due to sodium abundance in the earth's crust. The recent development of sodium ion batteries anode has been achieved by the use of selected carbon as an anode. The performance of the selected carbon materials such as the charge/discharge capacity, voltage profile and cyclic stability, depend strongly on the sizes, additives, electrolytes and structures. Based on the contribution of the carbon-based materials as a replacement of the sodium ion batteries anode, much improvement has been achieved. However, more investigations are still required in order to identify the suitable carbon materials that can provide and improve the anode properties. In the same vein, alloy materials have gained increasing effort as high capacity anode and their combination with carbon have contributed to the development of sodium ion batteries. In this review, we have accounted for the development of carbon-based materials and their composites with alloy materials as well as their prospects and challenges for sodium ion battery anodes.